Burnout pada Guru BK/Konselor Sekolah - Yandri, Hengki; Juliawati, Dosi (Konselor, 2017)
Basically every human being can experience burnout, including counselors, this happens because every human being must be experiencing the pressures in his life as in his work live. Burnout is a condition in individuals who have exhausted physically, mentally, emotionally and lack of motivation to work due to increasing work demands. If it is left alone, it will affect the performance of counselors in schools, so burnout in counselor should be followed up with appropriate solutions and healthy.